Testing a criticality framework for road networks in Auckland, New Zealand. Issue 1 (2nd April 2019) - Rebello, Kester; Jaggi, Karan; Costello, Seosamh; Blake, Daniel; Oo, May; Hughes, James; Egbelakin, Temitope
Abstract : Purpose: The purpose of this paper is to trial the application of a criticality framework for roads in an urban environment. The failure or disruption of critical transport routes can have substantial impacts on the economy and societal well-being. Determining the criticality of transport routes is thus of crucial importance for infrastructure providers, city planners and emergency management officials, as it enables appropriate resilience assessments and targeted improvement/intervention and investment strategies to be conducted. Design/methodology/approach: The authors summarise the proposed criticality framework developed by Hughes (2016) for road networks and apply and validate the framework to an area containing 907 km of roads in the central Auckland area of New Zealand. Following an initial trial of the framework, alterations were made to the framework logic, which included the introduction of a new criticality level to account for some roads providing minimal direct societal and economic benefit and a rationalisation step to ensure that road sections always link to others with either an equal or higher criticality. Findings: The modified framework and five-level criticality scale, when applied to the study area in central Auckland, is suitable for determining critical roads and can therefore assist with future assessments of road infrastructure resilience. Originality/value: The framework also has the potential to be applied more widely and adapted so that it is applicable for determining the criticality of other infrastructure types and in other settings, which would allow improved assessments within and across sectors.